Hybrid PV-Diesel-Battery System Performance in Tropical Malaysia: A Simulation Study - Abdullah Azraai bin Hasan; Nurul Afizah binti Adnan (YCMM, 2026)
Hybrid renewable energy systems (HRES) combining photovoltaic (PV) modules, diesel generators, and battery storage represent a compelling solution for distributed electrification in tropical regions. The equatorial climate of Peninsular Malaysia—characterised by high humidity (RH ≥ 78%), temperatures above 27°C, and pronounced cloud-induced irradiance transients—imposes performance penalties that remain insufficiently quantified. This study presents a comprehensive techno-economic simulation analysis of a 250-kWp hybrid PV-diesel-battery system modelled for Muadzam Shah, Pahang, Malaysia (3.07° N, 103.08° E) using HOMER Pro v3.16.2. Simulation outputs were validated against published Malaysian PV benchmarks. Results showed a mean simulated PR of 0.748 (±0.018), system efficiency of 13.9%, and LCOE of MYR 0.42/kWh, representing a 31.5% cost reduction over a diesel-only baseline. The mean REF reached 65.8%. Thermal derating due to elevated cell temperatures (T_cell = 56–70°C) was responsible for a 9.8% power output reduction. A Malaysian-specific humidity correction model is proposed, reducing cell temperature prediction error by 51.2% relative to the standard NOCT model.